Functional and antioxidant properties of protein-based films incorporated with mango kernel extract for active packaging - Zainal Arifin, Maryam 'Adilah; Bakar, Jamilah; Zainal Abedin, Nur Hanani (Elsevier, 2018)
This research is focused on developing active packaging by using food industries’ by-products. Soy protein isolate (SPI) and fish gelatin (FG) were used as the sources of biopolymers and different concentrations of mango kernel extracts (MKE) from 1 to 5% were added as natural antioxidants. Thicker and more translucent films (p < 0.05) were produced when a greater concentration of MKE was incorporated in both films. The mechanical test revealed that the addition of MKE increased the tensile strength of both films (p < 0.05), with higher tensile strength recorded in FG films than in SPI films. The incorporation of MKE significantly (p < 0.05) decreased the water solubility up to 22 and 33%, in FG and SPI films, respectively. The water vapor permeability (WVP) of SPI with the incorporation of MKE improved up to 10%. In contrast, FG films incorporated with MKE showed higher WVP in comparison with the control. The antioxidant activity increased with a greater concentration of MKE incorporated in both antioxidant films (p < 0.05) with more impact in SPI films compared to FG film in DPPH, FRAP and ABTS analysis. DPPH analysis on SPI films revealed the highest antioxidant activity (89%) with the inclusion of 5% MKE extract. Though both films were found to have the potential to be developed as antioxidant films, yet the overall observations revealed that SPI outperformed FG as active packaging films.